2021
DOI: 10.3389/fgene.2020.608650
|View full text |Cite
|
Sign up to set email alerts
|

Breed Ancestry, Divergence, Admixture, and Selection Patterns of the Simbra Crossbreed

Abstract: In this study, we evaluated an admixed South African Simbra crossbred population, as well as the Brahman (Indicine) and Simmental (Taurine) ancestor populations to understand their genetic architecture and detect genomic regions showing signatures of selection. Animals were genotyped using the Illumina BovineLD v2 BeadChip (7K). Genomic structure analysis confirmed that the South African Simbra cattle have an admixed genome, composed of 5/8 Taurine and 3/8 Indicine, ensuring that the Simbra genome maintains fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…Studies including African crossbred cattle with exotic breeds (e.g. Cheruiyot et al, 2018; Van der Nest et al, 2021) and/or studies addressing non‐environmental adaptative traits (Nanaei et al, 2020) were excluded. Henceforth, the review was compiled from 22 studies selected using three main criteria: (i) genome‐wide scanning for positive selection; (ii) genome‐wide analysis using genome sequences or SNP‐Chip data; and (iii) inclusion of indigenous African cattle (taurine, zebu, sanga, zenga).…”
Section: Discussionmentioning
confidence: 99%
“…Studies including African crossbred cattle with exotic breeds (e.g. Cheruiyot et al, 2018; Van der Nest et al, 2021) and/or studies addressing non‐environmental adaptative traits (Nanaei et al, 2020) were excluded. Henceforth, the review was compiled from 22 studies selected using three main criteria: (i) genome‐wide scanning for positive selection; (ii) genome‐wide analysis using genome sequences or SNP‐Chip data; and (iii) inclusion of indigenous African cattle (taurine, zebu, sanga, zenga).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the observed heterozygosity of Huaxi cattle exceeded the expected heterozygosity under the Hardy–Weinberg equilibrium. Hence, crossbreeding is still an important method to expand the genetic variation of modern cattle breeds [ 4 ]. High-intensity artificial selection might promote genetic progress, but it could lead to an increase in the population inbreeding level [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization is an important method for improving the desirable performance and overall genetic variation of cattle breeds [ 2 ]. Crossbreeding breeds combine the beneficial traits/genes of their purebred parental breeds, and have more superior production capacity than their parental inbred lines under the effect of heterosis [ 3 , 4 ]. Therefore, the introduction of excellent beef cattle breeds to cultivate specialized beef cattle breeds has become an important way to elevate the individual production efficiency of beef cattle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the expansion of agricultural society and human activities, extensive blending has occurred between different taurine and indicine populations, so there are more than over 800 live cattle breeds in the world [4]. Hybridization is a common strategy for the formation of modern livestock breeds and improving the undesirable performance of some cattle breeds, which leads to the superiority of a heterozygote over their purebred parental breeds in one or more traits [5]. In China, breeding specialized breeds through crossbreeding with commercial breeds has become an important way to improve the production efficiency of Chinese indigenous breeds.…”
Section: Introductionmentioning
confidence: 99%